2018
DOI: 10.1021/acs.jafc.8b01844
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ethylene Responsive miRNAs and Their Targets from Newly Harvested Banana Fruits Using High-Throughput Sequencing

Abstract: The roles of microRNAs (miRNAs) related to ethylene response in banana fruits remain unknown because many miRNAs are differentially expressed as the fruit ripens, making the identification of ethylene-responsive miRNAs difficult. Using newly harvested banana fruits (within 5 h after harvest) as material, we found that these fruit did not ripen when treated with 5 μL/L of ethylene for 12 h at 22 °C. Two miRNA libraries were generated from newly harvested banana fruits with and without ethylene treatment and seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…As with other plants, the majority of conserved miRNAs also had high abundance in E. ulmoides . Additionally, miR159, miR166 and miR396 had high expression levels in the majority of plants [5,42,44]. As expected, eu-miR159 was the most abundant in E. ulmoides , followed by eu-miR166a-3p, and eu-miR396 had moderate prevalence.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…As with other plants, the majority of conserved miRNAs also had high abundance in E. ulmoides . Additionally, miR159, miR166 and miR396 had high expression levels in the majority of plants [5,42,44]. As expected, eu-miR159 was the most abundant in E. ulmoides , followed by eu-miR166a-3p, and eu-miR396 had moderate prevalence.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies had shown that most conserved miRNAs were more abundantly expressed in various tissues and developmental stages of plants, whereas the abundance of non-conserved miRNAs was relatively low [42,43]. As with other plants, the majority of conserved miRNAs also had high abundance in E. ulmoides .…”
Section: Discussionmentioning
confidence: 92%
“…In banana, 12 novel and 128 known miRNAs were identified. Among these miRNAs, 22 were differentially expressed after ethylene regulation treatment and were involved in the ethylene response [ 30 ]. In Wang’s (2020) study between wild-type and LeERF1 transgenic tomato fruits, 9 miRNAs and 12 nat-siRNAs were found to be differentially expressed [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This showed that they were under the regulation of early auxin-responsive gene expression in the auxin signaling pathway [ 29 ]. An analysis of the differential expression of miRNAs in banana under ethylene treatment found that miR162a , miR167a , miR172a , and miR319a participated in ethylene-dependent fruit ripening [ 30 ]. All these results suggested that miRNAs play critical roles in plant development and fruit ripening by regulating ethylene targets, auxin, and other signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Two downstream TFs, EIN3 and EIN3-LIKE1 (EIL1) further induce numerous ETHYLENE RESPONSIVE FACTORs (ERFs) [5], which promote stress-responsive genes. Although the roles of ABA and ethylene in abiotic stress response are extensively studied, sheding light on the ABA/Et-controlled gene expression changes, it is unclear how and why ABA/Et also alter the levels of sRNAs in multiple species [99][100][101][102][103][104][105][106][107]. Excitingly, overexpression of some of these ABA-responsive sRNAs, like ath-miR168/393/394, renders arabidopsis more resistant to drought or salinity, suggesting that miRNAs are involved in the ABA-mediated drought response [108][109][110].…”
Section: Srnas and Abiotic Stress-related Hormones Abscisic Acid And Ethylenementioning
confidence: 99%